2017
DOI: 10.2147/amep.s132266
|View full text |Cite
|
Sign up to set email alerts
|

What factors facilitate the engagement with flipped classrooms used in the preparation for postgraduate medical membership examinations?

Abstract: BackgroundThe “flipped classroom,” a pedagogical model where typical lecture and homework elements are reversed, is being advocated in medical education to support the teaching of a large curriculum. However, research into the use of this model in postgraduate medical education, which requires the application of acquired knowledge, is limited. The aim of this study was to explore the barriers and facilitators to engagement with the flipped classroom model in preparation for the written element of postgraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…For example, the "flipped classroom" is an approach that could increase engagement, promote relevance, and cultivate the development of a network of learners by integrating asynchronous Webbased informational sessions with synchronous in-person, interactional formational activities. [38][39][40][41] Future research should explore ways to stimulate reciprocity in end-of-life Web-based education and training and develop strategies for cultivating a sense of commitment among trainees to implement the training in their practice settings and function as advocates for the expansion of palliative care system-wide.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the "flipped classroom" is an approach that could increase engagement, promote relevance, and cultivate the development of a network of learners by integrating asynchronous Webbased informational sessions with synchronous in-person, interactional formational activities. [38][39][40][41] Future research should explore ways to stimulate reciprocity in end-of-life Web-based education and training and develop strategies for cultivating a sense of commitment among trainees to implement the training in their practice settings and function as advocates for the expansion of palliative care system-wide.…”
Section: Discussionmentioning
confidence: 99%
“…There are also barriers that impair the engagement of students in the flipped classroom. Jesurasa and colleagues reported that the design of the flipped classroom, such as the degree to which the classroom is flipped, the challenges to acquiring fundamental knowledge, limitation of larger class sizes, teaching styles, and students' expectation of the instructors, may all have an effect on students' interest in the flipped classroom [12]. It was reported that students who favored traditional lectures over the flipped classroom thought the flipped classroom encouraged rushed learning, and made them feel behind and inadequate [13].…”
Section: Introductionmentioning
confidence: 99%
“…This study findings reported here indicate that the flipped classroom approach, which is increasingly advocated for in medical education, can have positive impact on learning outcomes and experiences in the context of online graduate-level public health education (Jesurasa, Mackenzie, Jordan, & Goyder, 2017;Merzel, Halkitis, & Healton, 2017). To quote one of the students, "THIS [emphasis original] is how a graduate level course should be taught."…”
Section: Discussionmentioning
confidence: 84%